Rasio Keuangan dalam Memprediksi Pertumbuhan Laba Pada Perusahaan Tambang Minyak dan Gas Bumi Yang Terdaftar Di Bursa Efek Indonesia, Periode 2012-2016 - Nenik Mey Yetty; Prihat Assih; Gaguk Apriyanto (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2018)
This study aimed to examine the influence of independent variabel : Current ratio (X1), Debt to Equity Ratio (X2), Total Asset Turnover (X3), Net Profit Margin (X4) and Return on Equity (X5) the Growth Profit (Y) in the period 2012-2016. The research is using secondary data that obtained from Bursa Efek Indonesia (BEI). Sampling technique that used on this research is purposive sampling. The number of samples in this research is about 7 company. Hypothesis testing is done by using multiple linear regression analysis. Result of the research shows that theres positive influence between variabel current ratio, debt to equity ratio, total asset turnover, net profit margin. Return on equity proved no significant effect on against the growth of profit in oil and word gas campany in period 2012-2016.